2019
DOI: 10.1177/0271678x19854640
|View full text |Cite
|
Sign up to set email alerts
|

What does computational fluid dynamics tell us about intracranial aneurysms? A meta-analysis and critical review

Abstract: Despite the plethora of published studies on intracranial aneurysms (IAs) hemodynamic using computational fluid dynamics (CFD), limited progress has been made towards understanding the complex physics and biology underlying IA pathophysiology. Guided by 1733 published papers, we review and discuss the contemporary IA hemodynamics paradigm established through two decades of IA CFD simulations. We have traced the historical origins of simplified CFD models which impede the progress of comprehending IA pathology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 218 publications
(263 reference statements)
0
85
0
1
Order By: Relevance
“…Indeed, we do not argue that hemodynamic studies of the CBF such as MR-SPECT should have a lesser importance, on the contrary, we employed these techniques as the gold standard for clinical diagnosis. Our aim was to take the CFD a step further towards its ultimate clinical goal as a clinical diagnostic and decision-making tool 12 . In this work we clearly demonstrate the power of CFD as decision making tool, even though the study was performed retrospectively, as CFD analysis was able to predict the root causes of hemodynamic insufficiency in our patient cohort, and to demonstrate why they did not respond to medical therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, we do not argue that hemodynamic studies of the CBF such as MR-SPECT should have a lesser importance, on the contrary, we employed these techniques as the gold standard for clinical diagnosis. Our aim was to take the CFD a step further towards its ultimate clinical goal as a clinical diagnostic and decision-making tool 12 . In this work we clearly demonstrate the power of CFD as decision making tool, even though the study was performed retrospectively, as CFD analysis was able to predict the root causes of hemodynamic insufficiency in our patient cohort, and to demonstrate why they did not respond to medical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that the Newtonian assumption used in CFD models of cerebral blood flow is an inappropriate over-relaxed assumption 12,59 . To model the non-Newtonian shear thinning blood properties, the Carreau-Yasuda 60 model was used.…”
Section: Cfd Procedure Large Eddy Simulation Of Pulsatile Non-newtonmentioning
confidence: 99%
See 2 more Smart Citations
“…CFD technique can reduce unnecessary interventional angiography effectively and help doctors to diagnose pathological conditions [22,23] . Moreover, CFD can be applied to assess the risk of rupture and pressure of the intracranial aneurysm, thereby improving the understanding of the biomechanics of the aneurysms [24] .…”
Section: Cfd Is a Well-established Technique That Provides Comprehensmentioning
confidence: 99%